Validation of an LC–MS/MS salivary assay for glucocorticoid status assessment: Evaluation of the diurnal fluctuation of cortisol and cortisone and of their association within and between serum and saliva. Issue 163 (October 2016) - Mezzullo, Marco; Fanelli, Flaminia; Fazzini, Alessia; Gambineri, Alessandra; Vicennati, Valentina; Di Dalmazi, Guido; Pelusi, Carlotta; Mazza, Roberta; Pagotto, Uberto; Pasquali, Renato
Highlights: LC–MS/MS assayed salivary cortisol and cortisone parallels serum levels daily rhythm. Cotton swab device Salivette ameliorates saliva collection and analysis. Salivary cortisol reflects serum free cortisol and HPA axis activation. Salivary cortisone reflects overall cortisol exposure. Abstract: Salivary steroid testing represents a valuable source of biological information; however, the proper measurement of low salivary levels is challenging for direct immunoassays, lacking adequate sensitivity and specificity and causing poor inter-laboratory reproducibility. Liquid chromatography-tandem mass spectrometry (LC–MS/MS) has overcome previous analytical limits, often providing results deviating from previous knowledge. Nowadays, LC–MS/MS is being introduced in clinical laboratories for salivary cortisol testing; however, so far only a few studies have reported thorough biological validation based on LC–MS/MS data. In this study, we provide a thorough analytical, pre-analytical and biological validation of an LC–MS/MS method for the measurement of salivary cortisol (F) and of its inactive metabolite cortisone (E). Analytes were extracted from 50 μl of saliva, were then separated in 7.5 min LC-gradient and detected by negative electrospray ionization—multiple reaction monitoring. The reliability of a widely diffused collection device, Salivette ®, was assessed and the overall procedure was validated. The diurnal cortisol and cortisone fluctuation in saliva and serum was described by a four paired collection protocol (8 am, 12 am, 4 pm and 8 pm) in 19 healthy subjects. The assay allowed the quantitation of F and E down to 39.1 and 78.1 pg/ml, with an imprecision range of 5.5–9.5%, 3.9–14.1% and 2.6–14.4%, and an accuracy range of 105.5–113.1%, 88.5–98.7% and 90.7–96.7% for both analytes at low, medium and high levels, respectively. Salivette ® provided comparable results and better precision (CV < 1.0%) as referred to direct spitting (CV < 13.0%). A parallel diurnal rhythm in saliva and serum was observed for cortisol and cortisone, with values lowering from the morning to the evening time points (P < 0.0001). While salivary E linearly correlated to total serum F (R 2 = 0.854, P < 0.001), salivary F showed an exponential relationship (R 2 = 0.903, P< 0.001) with serum F reflecting the free circulating fraction. A non linear association between E and F was observed in saliva (R 2 = 0.941, p < 0.001) consistent with the type II 11β-HSD activity. We concluded that our LC–MS/MS method allowed a sensitive evaluation of salivary levels of cortisol and cortisone. The simultaneous determination of both hormones in saliva allowed the differential estimation of the active and of the total glucocorticoid exposure over the daytime. The assay could provide further insight into the comprehension of normal and dysfunctional glucocorticoid circadian rhythm.